Association between vaccination, viral antibodies, and asthma prevalence in the U.S.: insights from NHANES (1999–2020) - Yang, Zonghui; Guo, Jia; Cheng, Manman; Zhang, Youwen; Chen, Zhi; Wen, Jie; Shan, Fenglian (Frontiers in Allergy, 2025)
ObjectiveThis investigation aimed to explore the differences in asthma prevalence among various demographic groups in the U.S., focusing on factors related to vaccination and viral antibodies.MethodsThe study analyzed data from 37,445 individuals collected through the National Health and Nutrition Examination Survey between 1998 and 2020. Employing weighted sampling methods, the analysis considered the stratification and clustering typical of the survey's design. It particularly examined how age, race, income, smoke, education, and gender factors influence both the prevalence and severity of asthma.ResultsThis study aims to elucidate disparities in asthma prevalence across the U.S. population by examining the roles of demographic characteristics and factors related to vaccination and viral antibodies. It revealed a significant correlation between asthma prevalence and patient demographics, including age, gender, income, smoke, education, and race. We found that asthma patients were mostly found in participants with lower economic level (2.7 vs. 2.87). Non-Hispanic black women age exhibited a higher likelihood of asthma, at 17.7%, compared to non-Hispanic whites and Mexican Americans. Asthma prevalence peaks between the ages of 20 and 30 and has shown a rising trend over the years. Regarding vaccinations, hepatitis A, hepatitis B, pneumococcal, and HPV vaccines were associated with an increased risk of asthma. Conversely, patients testing positive for hepatitis A virus and core hepatitis B virus antibodies demonstrated a lower prevalence of asthma. Additionally, asthmatic patients showed lower average measles virus and rubella antibodies levels, at 0.53 and 3.32, respectively, compared to non-asthmatic individuals. Notably, asthma incidence was lower in herpesvirus I-positive patients (OR: 0.895, CI, 0.809%–0.991%), while herpesvirus II-positive patients displayed a higher incidence of asthma (OR: 1.102, CI, 0.974%–1.246%).ConclusionThe study findings underscore the significant prevalence of asthma and its correlation with population demographics, vaccination rates, and serum viral antibodies. These results highlight the importance of implementing tailored public health interventions.